Multigenerational migration of fall armyworm, a pest insect. Issue 11 (1st November 2019) - Westbrook, J.; Fleischer, S.; Jairam, S.; Meagher, R.; Nagoshi, R.
Abstract: Multigenerational insect migration commonly expands poleward, but meteorological influences are not clearly understood. We coupled biological and physical processes for the agricultural and invasive pest Spodoptera frugiperda (fall armyworm), by modeling its seasonal migration, and comparing simulated migrations to observed captures, and population genetic markers, at a continental scale. Simulations corroborated the spatial distribution and mixing of Texas and Florida source populations defined by genetic haplotypes. Positive relationships were found between first weeks of simulated and observed immigration, and between genetic and simulated metrics. The capacity to project biotic‐, migratory‐, and meteorology‐induced shifts in insect distributions will aid strategic implementation of crop protection measures and economic analyses of host‐resistant germplasm deployment in response to a warming climate.